Respuesta :
Answer:
C
Step-by-step explanation:
So we have the expression:
[tex](x+y+3)\times(y+1)[/tex]
To multiply, use the distributive property. Multiply (y+1) to each term on the left:
[tex]=x(y+1)+y(y+1)+3(y+1)[/tex]
Distribute the variables:
[tex]=(xy+x)+(y^2+y)+(3y+3)[/tex]
Rearrange them to combine like terms:
[tex]=y^2+xy+y+3y+x+3\\=y^2+xy+4y+x+3[/tex]
The correct answer is C.
Edit: Typo
[tex](x+y+3)\cdot(y+1)=\\\\=(x+y+3)\cdot y+(x+y+3)\cdot1=\\\\=xy+y^2+3y+x+y+3=\\\\=\boxed{y^2+xy+4y+x+3}[/tex]
Answer C.